2019
DOI: 10.1111/bjdp.12278
|View full text |Cite
|
Sign up to set email alerts
|

Expressivity in children's drawings of themselves for adult audiences with varied authority and familiarity

Abstract: This study investigated whether children's expressive drawings of themselves vary as a function of audience authority and familiarity. One hundred and seventy‐five children, 85 boys and 90 girls, aged between 8 years 1 months and 9 years 2 months (M = 8 years 5 months) were allocated into seven groups: a reference group (n = 25), where no audience was specified, and six audience groups (n = 25 per group) varying by audience type (policeman vs. teacher vs. man) and familiarity (familiar vs. unfamiliar). They dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The drawings were then rated through a content analysis, which revealed the use of seven expressive graphic cues for each emotion. First, in line with previous research, we expect children to use a higher number of graphic cues and/or different types of graphic cues when drawing for a specified audience (male and female audience conditions) than when drawing with no audience specified (control condition) (Burkitt, 2017; Burkitt et al, 2011, 2019; Burkitt & Watling, 2013). Second, because children apply their developing representations of gender to interpret the world around them, we expect children to alter the content of their drawings depending on whether they draw for a male or a female audience (Leaper & Freidman, 2007).…”
supporting
confidence: 69%
See 3 more Smart Citations
“…The drawings were then rated through a content analysis, which revealed the use of seven expressive graphic cues for each emotion. First, in line with previous research, we expect children to use a higher number of graphic cues and/or different types of graphic cues when drawing for a specified audience (male and female audience conditions) than when drawing with no audience specified (control condition) (Burkitt, 2017; Burkitt et al, 2011, 2019; Burkitt & Watling, 2013). Second, because children apply their developing representations of gender to interpret the world around them, we expect children to alter the content of their drawings depending on whether they draw for a male or a female audience (Leaper & Freidman, 2007).…”
supporting
confidence: 69%
“…For instance, when asked to draw an array of bricks, children do not draw the same way when they are explicitly told that someone would use their drawing to understand the exact positions of the bricks (audience condition) compared to when they are not (control condition). There is also strong evidence that children alter expressive aspects of their drawings depending on audience-related information (Burkitt, 2017; Burkitt & Watling, 2013; Burkitt et al, 2011, 2019). In their studies, Burkitt and colleagues found that, from the age of 6, the way children depict emotions (i.e., happiness and sadness) in their drawings varies as a function of both the existence and the type of audience.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In relatively recent years a number of studies have examined the development of children's ability to represent expressive faces, either explicitly requiring an emotional connotation or proposing an evocative theme (see Burkitt et al, 2019, Laghi et al, 2014Pezzica et al, 2016;, as recent examples including references to other relevant papers). According to these studies some properties of drawings, such as figure size, shape, or color, do possess an emotional meaning that can be investigated systematically.…”
Section: Introductionmentioning
confidence: 99%